Farewell to flexicurity? Austerity and labour policies in the European Union. (August 2018) - Hastings, Thomas; Heyes, Jason
For the past decade the European Commission has urged EU member states to pursue 'flexicurity' policies aimed at achieving employment growth and social inclusion. However, the economic crisis and turn to austerity across the EU has presented the flexicurity model with a substantial challenge. This article argues that since 2008 labour policies across the EU have exhibited shared tendencies, but support for measures that might contribute to the achievement of the security aspects of flexicurity has been substantially weakened. In developing this argument, the article presents findings from a cluster analysis and detailed investigations of labour policies in EU member countries. The article also discusses the implications of the findings for comparative institutional analysis. It highlights differences in the approaches of countries that are commonly treated as members of the same institutional family, as well as similarities in the policies adopted by countries commonly associated with different 'varieties' of capitalism.